Reimagining Space through Fluid Boundaries: Water as a Dynamic Force in The Hungry Tide - Paudyal , Janak (Bon Voyage, 2025)
This paper explores Amitav Ghosh’s The Hungry Tide as a literary intervention that reorients spatial imagination by foregrounding water as a dynamic and destabilizing force. Ghosh’s novel challenges traditional land-based narratives that rely on fixed borders and linear histories and thus situates the fluid geographies of the Sundarbans as central to its thematic and narrative structure. In conversation with the theoretical ideas of Steve Mentz and John R. Gillis, the analysis draws upon concepts from the blue humanities to examine how water disrupts binary divisions between land and sea, human and non-human, settled and nomadic life. Through characters such as Piyali Roy and Fokir Mondol, Ghosh constructs a fluid epistemology that resists the certainties of cartographic, colonial, and nationalist logics. Finally, the paper argues that The Hungry Tide not only dramatizes the ecological and cultural precarity of coastal life but also proposes a reimagined understanding of space, identity, and history in the Anthropocene.